2021
DOI: 10.3389/fnagi.2021.735933
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Microbiota Sensing – Free Fatty Acid Receptor 2 Signaling Ameliorates Amyloid-β Induced Neurotoxicity by Modulating Proteolysis-Senescence Axis

Abstract: Multiple emerging evidence indicates that the gut microbiota contributes to the pathology of Alzheimer’s disease (AD)—a debilitating public health problem in older adults. However, strategies to beneficially modulate gut microbiota and its sensing signaling pathways remain largely unknown. Here, we screened, validated, and established the agonists of free fatty acid receptor 2 (FFAR2) signaling, which senses beneficial signals from short chain fatty acids (SCFAs) produced by microbiota. The abundance of SCFAs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…SCFAs represent an emerging target for the aging brain and age‐related neurodegenerative diseases in recent years. Although it has been shown that SCFAs can directly activate specific G protein‐coupled receptors (GPCRs), including GPR43, GPR41, and GPR109a (Dalile et al, 2019), the expression of these GPCRs is detected in several cell types in the central nervous system, including neurons and glia (Erny et al, 2015; Razazan et al, 2021; Tran & Mohajeri, 2021). However, the exact mechanism by which SCFAs is involved in age‐related neurodegenerative diseases is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCFAs represent an emerging target for the aging brain and age‐related neurodegenerative diseases in recent years. Although it has been shown that SCFAs can directly activate specific G protein‐coupled receptors (GPCRs), including GPR43, GPR41, and GPR109a (Dalile et al, 2019), the expression of these GPCRs is detected in several cell types in the central nervous system, including neurons and glia (Erny et al, 2015; Razazan et al, 2021; Tran & Mohajeri, 2021). However, the exact mechanism by which SCFAs is involved in age‐related neurodegenerative diseases is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…GraphPad Prism 7.0 was used to accomplish the statistical analysis. A sample size was estimated based on previous neuroblastoma cell line for neurodegenerative studies (Razazan et al, 2021; Wu et al, 2022) to obtain biometrical sample size estimation and the assumptions of a power of 0.8 and a type I error rate of 0.05. Data was expressed as median ± interquartile range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that the gut microbial population (the microbiome or microbiota) collectively contains 100 times more genes than humans and makes numerous compounds, nutrients, and vitamins that are required for the epigenetic fine tuning of brain genes’ functions, as reviewed elsewhere [ 34 ]. As an example, the gut microbiota produces short-chain fatty acids (SCFAs), which are well-known epigenetic modifiers and protect neurons via free fatty acid receptor 2 (FFAR2) signaling [ 141 ].…”
Section: Microglia and Astrocytes The Ambassadors Of Microbiome Commu...mentioning
confidence: 99%
“…Acetate, one of the SCFAs, could suppress neuroinflammation and attenuate perioperative neurocognitive disorders by binding to GPR43 according to a recent research (14). The activation of GPR43 also ameliorates the accumulation of amyloid-β and neuroinflammation in Alzheimer disease (16). However, whether GPR43 exerts an anti-neuroinflammation effect by interacting with SCFAs in SAE or not is still unclear.…”
Section: Introductionmentioning
confidence: 99%